Endocarditis Complicated by Septic Embolic Induced Acute Myocardial Infarction - Postma, Warner Rintje; Hermanides, Renicus Suffridus; Bruinsma, George Brandon Bravo; Hof, Arnoud Vant (Cardiology and Cardiovascular Medicine, 2020)
A 58-year old woman with an endocarditis of the aortic valve developed an acute anterior STEMI. Manual thrombus aspiration yields an embolus with a coccoid bacterium. The patient underwent immediate surgery with an aortic bioprosthesis and a coronary artery bypass graft (CABG) with a saphenous vein to the distal LAD.